Effect of high-temperature stress on phenylpropanoid biosynthesis and antioxidant activities of Acer palmatum - Yoon, Jiwon; Kwon, Haejin; Lim, Jinsu; Kim, Kihyun; Seo, Hyewon; Uddin, Md Romij; Manickam, Kohila; Kim, Jae Kwang; Park, Sang Un (Journal of Aridland Agriculture, 2024)
Acer palmatum is an ornamental tree grown in East Asia and is exposed to the possible hazards of global climate changes and increased temperatures. In this context, a study was conducted in a greenhouse at the experimental farm of Chungnam National University, Daejeon, South Korea from April to August 2023, to explore the consequences of high temperature stress on A. palmatum and assess the phenylpropanoid biosynthesis, antioxidant activity, and chlorophyll content in its leaves. One-year-old seedlings were treated at 40 °C for 1-3 days to determine the phenolic and flavonoid content, chlorophyll concentrations, and antioxidant activity at various intervals. The highest phenylpropanoid, total phenolic compound, and total flavonoid contents were observed during the first 2 days of high temperature treatment and reduced afterwards. Regarding the duration of the plant’s exposure, 1 day of exposure was associated with the highest antioxidant level assessed with DPPH and ABTS assays, while antioxidant activity was lowest under a long duration. The chlorophyll B content increased 2-fold with 1 day of heating exposure, in contrast to the levels of chlorophyll A and B. However, A. palmatum benefitted from a moderate level of heat stress, which stimulated the development of protective biochemical responses without developmental features. At the same time, extended exposure compromised the physiological health of the plant, reducing the phenolic content, antioxidant activity, and chlorophyll content.